Cytomegalovirus duodenitis in immunocompetent patients: what else should we look for? - Costa, Dalila Amélia Amorim (2017)
Cytomegalovirus (CMV) infection is a well-recognised complication of immunodeficiency, although the burden of CMV disease in immunocompetent adults is still unknown. We present the case of a 54-year-old male patient admitted due to severe diarrhoea, epigastric pain and fever. Initial diagnostic workup revealed pericardial and pleural effusion, enlarged abdominal lymph nodes and mild elevation of liver enzymes. CMV serology was IgM positive, and upper endoscopy revealed proximal enteritis. Histology and immunohistochemistry of duodenal samples confirmed CMV disease. An extensive investigation of possible immunodeficiency was conducted with positron emission tomography (PET) scan revealing an abnormal hypermetabolic pulmonary nodule. The patient underwent a right superior lobectomy which, on analysis, confirmed an atypical bronchopulmonary carcinoid tumour. We report this case to reinforce the importance of considering CMV infection as a differential diagnosis in apparent immunocompetent patients and to emphasise the importance of looking for any condition that may cause any degree of immune dysfunction.